The Commuting Paradigm Drift and Shift in Gauteng Province, South Africa: Transport Dimensions and Implications - Chakwizira, James; Bikam, Peter; A. Adeboyejo, Thompson (International Journal of Engineering and Technology, 2018)
South Africaâ€™s extreme â€œspatial fragmentation, with large numbers of poor people dependent on public transport living far from the urban core, poses a severe challenge for access to workâ€ [1]. The â€œ2003 National Transportation Survey [2] revealed that about 24 percent of workers in Gauteng spend more than an hour travelling to work, with 31 percent of households spending more than 10 percent of their income on transportâ€ [3]. â€œSouth African cities are evolving in the direction of being more multimodal or polycentric, which makes it more difficult to provide an efficient public transportation systemâ€ [4, 5]. This paper based on a desktop survey and insights from key stakeholders confirm that commuting paradigm drifts and shifts manifest themselves in Gauteng as traffic congestion, long commuting trips, high commuting costs, spatially extensive and a sprawled transportation network system. To respond to the multiple transport dimensions and implications, the paper recommends that a repertoire of practical, innovative strategies and measures be implemented such as expanding the bus rapid transport (BRT) Rea Vaya beyond the current phases, expanding the Gautrain line as well as the implantation of transit orientated development (TOD) as part of converting Gauteng province into a smart transportation and commuting region in South Africa.Â Â